2021
DOI: 10.1071/is20065
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics and biogeography of leptonetid spiders (Araneae : Leptonetidae)

Abstract: Leptonetidae are rarely encountered spiders, usually associated with caves and mesic habitats, and are disjunctly distributed across the Holarctic. Data from ultraconserved elements (UCEs) were used in concatenated and coalescent-based analyses to estimate the phylogenetic history of the family. Our taxon sample included close outgroups, and 90% of described leptonetid genera, with denser sampling in North America and Mediterranean Europe. Two data matrices were assembled and analysed; the first ‘relaxed’ matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Europe, and all of the species in Leptoneta are morphologically, and geographically misplaced 5 (Ledford et al, 2021). Although Seo transferred many species of Leptoneta to Falcileptoneta (2015) 18 , more than ten species of Korean leptonetids are still remaining in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Europe, and all of the species in Leptoneta are morphologically, and geographically misplaced 5 (Ledford et al, 2021). Although Seo transferred many species of Leptoneta to Falcileptoneta (2015) 18 , more than ten species of Korean leptonetids are still remaining in this genus.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of UCE-derived data suggested that the subfamily Archoleptonetinae (which includes only two genera, the cribellate Archoleptoneta and the ecribellate Darkoneta) do not nest within the clade containing other leptonetids (Ram ırez et al, 2021). This subfamily then was elevated to family rank as Archoleptonetidae by Ledford et al (2021). This phylogenetic placement seems to be sensitive to data class and/or taxon sampling because, the transcriptomic data treated as amino acids, with three genera sampled, suggest that Archoleptoneta (Archoleptonetidae), Calileptoneta and Leptoneta (both Leptonetidae) form a clade (Kallal et al, 2021a).…”
Section: Leptonetidae and Archoleptonetidaementioning
confidence: 99%
“…Not only spiders, but all arachnids prominently feature in biogeographic studies. Given the old age of many arachnid lineages, empirical studies have helped to reconstruct past events as old as the breakups of Pangea and Gondwana (Boyer et al, 2007;Rix and Harvey, 2012;Xu et al, 2015;Clouse et al, 2017;Chousou-Polydouri et al, 2018) and diversification on major land masses (Chamberland et al, 2018;Esposito and Prendini, 2019;Turk et al, 2020;Ledford et al, 2021;Turk et al, 2021b). Arachnids have featured in research of evolutionary consequences of global climatic oscillations (Luo et al, 2020) and, at finer geographical scales, of glaciation events (Xu et al, 2016;Santibañez-Loṕez et al, 2021), tectonic movements (Opatova et al, 2016), formation of rivers and mountain chains (Hedin et al, 2013;Emata and Hedin, 2016;Xu et al, 2018;Schramm et al, 2021), aridification (Abrams et al, 2019), and other biotic/abiotic events (Bond et al, 2020) as well as processes involved with subterranean colonization and diversification (Harms et al, 2018).…”
Section: Arachnids As Biogeographical Model Organismsmentioning
confidence: 99%